(NsOBRANIE SO^INENIJ W DWENADCATI TOMAH(B; s (NrASSKAZY(B; (NfELXETONY(B; (N`MORISTI^ESKAQ SMESX(B: [1880-1883] / s (N~ASTX (B1s - (N~EHOW(B, (NaNTON pAWLOWI^s ((NmOSKWA(B: s (NpRAWDA(B, s, 1985)
(Nw PERWYJ TOM WO[LI RASSKAZY(B, (NFELXETONY(B, (N@MORISTI^ESKAQ SMESX (B(1880 - 1883), (NWKL@^ENNYE a(B. (Np(B. (N~EHOWA W SOBRANIE SO^INENIJ I NE WKL@^ENNYE(B.s
rus
Keywords: (NpOWESTI I RASSKAZYs; (NfELXETONYs -- (NkOMEDIQs